The breathing frequency changes during swimming by using respiratory valves and tubes - Kapus, J.; Strumbelj, B.; Usaj, A.; Kapus, V. (Biomechanics and Medicine in Swimming X, 2006)
The purpose of the present study was to ascertain the influence of a respiratory valve and tubes (RV) during three different swimming tests (submaximal and maximal 200-m front crawl swim and front crawl swimming to exhaustion) on a breathing frequency and selected biomechanical parameters. Twelve former competitive male swimmers performed each swimming test twice: first, with RV, and second, without RV. Swimming with RV induced slower maximal 200-m front crawl swim and shorter front crawl swimming to exhaustion in comparison with swimming without RV. Furthermore strategies of the breathing frequency during submaximal and maximal swimming tests were also differed between swimming with RV and swimming without RV. Therefore, it may be concluded that when RV is used for measuring respiratory parameters during swimming, a different pattern of breathing (comparing to swimming without RV) may occur.